Propuesta de plan maestro del área de conversación municipal Almedra - Pezo Seijas, Jose Augusto (2005)
The present thesis, Proposal of Plan Teacher of the Area of Conservation Municipal Almond", this guided to contribute in the planning and rational use of the resources being an administration too!, for the Entity Persuaders of Services of Reparation Moyobamba SRLtda, patron of the project. Entity that gives the water to 40 000 inhabitants ofthe city. This work was carried out with the purpose ofto identify and to describe the socioeconomic processes that determine the systematic changes in the supply ofthe resource hydrological. For the analysis of the reality of the study area he/she was carried out by means of the processes of Determination of the study area, Diffusion of the process, Revision and validation of the existent information, Summary of the information, Baboration of specific studies, Zonificacion of the area, and Elaboration of the Programs and Routines of the area. Having the participation in the shops and the pocess to the residents of the sectors of the Shainas and Mishquiyaquillo, and the Til.lages of The Orange grove and made Alfarillo that it contributed to strengthen the process. The study area, embraces an extension of 1620 hectares a perimeter of 19 781.00 lineal meters. The biggest existent information corresponds to the technical file of sustentation of creation of the area elaborated by the PETT, and basecl on he/she was defined it the realization of studies of Flora where you can specify that the most ñ:nportant species in the structure of the primary forest are: Huacapú, Caraña, Cashamoena, Almond, Huriamba, Ushunquiro, these species represent 60.13% of the sructure ofthe forest, considering trees from the 5 cm. ofDAP, to regarding the Index al Value of Importance, The distribution of the trees in relation to the classes diamétricas is in positive exponential form, interpreted by the presence of a smaller lll:IDlber oftrees of diameters. In the fauna study they were the following species. With regard to amphibians eme has the presence ofthe family Bufonidae with a species 1 Snort margaritiferus. With ~d to reptiles of the sub order Colubridae with the presence of a species Afaninga Chironius fucus}, and three of sub order Viperidae; Parrot Mashes (Bothriopsis atineata), Mattress (Bothropps atrox}, and Shushupe (Lachesis muta). With regard to &irds he has been able to register 19 families; Tinarnidae, Cathartidae, Accipitridae, hkonidae, Ramphastidae, Picidae, Tyrannidae, Troglodytidae, Emberizidae, xvu Thraupidae, Contingidae, Trogonidae, Corvidae. In the study area he/she has registered so much for avistamiento, rakes, sounds and he/she interviews with residents of the area, the existence of 12 families of mammals that you/they correspond to 15 species. Great diversity of butterflies of showy colours has been observed, as the gender: Papilionidae, Pieridae and Nymphalidae with their Sub families; Nymphalinae, Charaxinae, Heliconiinae, Brassolinae, Satyrinae, Morphinae. Of the socioeconomic and environmental Study it is observed, alone 12.9QO/o of the farmers is devoted to the livestock upbringing 1 vaccinate especially for the sector the Shainas and the Village Alfarillo, with a maximum of livestocks of 25 and a minimum of one. The residents are consciences ofthis problem and they manifest their limitations and the threat that it would be with the change of cultivations of coffee for grasses reducing the capacity of retention of the resource hydrological by m~s of the biological mattress. The cultivation of coffee is the biggest agricultura! work that you/they carry out and it is sold in its majority in the companies and middlemen of the city of ~oyobamba, the varieties of coffee that are cultivated are Caturra, Catimor that are cultivations in its 6 year-old recent great extension. One has the national variety that embraces the biggest extension in the area and they exist in you stain them observables in the area they have an antiquity from 15 to 20 years. The production on the average gives 17.56 qq/ha. in parchment. The months of crop they go in the low parts ofMarch to June and the high parts ofMay to September. The number average of sowed hectares of coffee for farrner this in 2.5 there are. Inside the plagues and illnesses of the cultivation of coffee the present affectation is 8.41 % for Arañero (Corticium kileroga), 10.03% Dril! (Hypothenemus hampei), 8.09% Eye of Chicken (Mycena citricolor), 1.94% Roya (Hernileia vastratix), 5.83% for Black Foot (Rossellinianm sp.), and 65. 70% of cultivations that are not relatively affected. The organizations that support and they manifested their commitment in forrning synergies for the rational use of the resources they are: Provincial municipality of Moyobamba, German Technical Cooperation (GTZ-PDRS), 1 Govem Regional of San Martin - 1 Project Special High May (PEAM), 1 Project Andean Basins, Ministry of Agriculture Handling ofNatural Resources ofthe Sierra South (MARENASS), National Institute of Natural Resources (INRENA), Entity Prestadora of Services of Reparation xviii \foyobamba EPS-M. SRLtda, Rural Beats, Committee of Administration of Areas of ~fonicipal Conservation, Units ofLocal Administration. The objective of the Plan Teacher is to be a document it guides, for the administration and administration of the Area of Conservation Municipal Almond, on tbe part of the Municipal Government of Moyobamba through the Management of ~iunicipal Services and environment, and the Entity Prestadora of Services of Reparation SRLtda, through the Prograrn of Preservation of the environrnent that is in mrrow coordination with the Units of Local Administration, the Rural Beats and Committees of Autofensa and Development. It will be an instrument of local administration, dynamics with a period of four year-old validity. The priorities identified in the process that you/they are the tree Almond (Pnmus amygdalus), the butterfly Maria Elena (Morpho menealus), the bird Huauto or mount turkey (Aburri aburria) and the Bromélida (Tillandsia mureana). By means of the process you Zonificacion and based on the Article 23º of the law of protected natural areas 26834. lt is contemplated the following areas: Area of Sttict Protection Strict 440.78 has, Area of Tourist and Recreational Use 83.26 has, Area ofspecial Use 23.14 has, Area ofRecovery 130.99 has. It was possible to identify me following programs: lt prograrns ofHandling ofNatural and Cultural Resources, it Programs of Use Public, it Programs from Support to the Administration, Prograrn of ~.lonitored and Evaluation. With an 1 mount for four years of 135 050.000 New Suns. The present thesis, Proposal of Plan Teacher of the Area of Conservation Municipal Almond", this guided to contribute in the planning and rational use of the resources being an administration too!, for the Entity Persuaders of Services of Reparation Moyobamba SRLtda, patron of the project. Entity that gives the water to 40 000 inhabitants ofthe city. This work was carried out with the purpose ofto identify and to describe the socioeconomic processes that determine the systematic changes in the supply ofthe resource hydrological. For the analysis of the reality of the study area he/she was carried out by means of the processes of Determination of the study area, Diffusion of the process, Revision and validation of the existent information, Summary of the information, Baboration of specific studies, Zonificacion of the area, and Elaboration of the Programs and Routines of the area. Having the participation in the shops and the pocess to the residents of the sectors of the Shainas and Mishquiyaquillo, and the Til.lages of The Orange grove and made Alfarillo that it contributed to strengthen the process. The study area, embraces an extension of 1620 hectares a perimeter of 19 781.00 lineal meters. The biggest existent information corresponds to the technical file of sustentation of creation of the area elaborated by the PETT, and basecl on he/she was defined it the realization of studies of Flora where you can specify that the most ñ:nportant species in the structure of the primary forest are: Huacapú, Caraña, Cashamoena, Almond, Huriamba, Ushunquiro, these species represent 60.13% of the sructure ofthe forest, considering trees from the 5 cm. ofDAP, to regarding the Index al Value of Importance, The distribution of the trees in relation to the classes diamétricas is in positive exponential form, interpreted by the presence of a smaller lll:IDlber oftrees of diameters. In the fauna study they were the following species. With regard to amphibians eme has the presence ofthe family Bufonidae with a species 1 Snort margaritiferus. With ~d to reptiles of the sub order Colubridae with the presence of a species Afaninga Chironius fucus}, and three of sub order Viperidae; Parrot Mashes (Bothriopsis atineata), Mattress (Bothropps atrox}, and Shushupe (Lachesis muta). With regard to &irds he has been able to register 19 families; Tinarnidae, Cathartidae, Accipitridae, hkonidae, Ramphastidae, Picidae, Tyrannidae, Troglodytidae, Emberizidae, xvu Thraupidae, Contingidae, Trogonidae, Corvidae. In the study area he/she has registered so much for avistamiento, rakes, sounds and he/she interviews with residents of the area, the existence of 12 families of mammals that you/they correspond to 15 species. Great diversity of butterflies of showy colours has been observed, as the gender: Papilionidae, Pieridae and Nymphalidae with their Sub families; Nymphalinae, Charaxinae, Heliconiinae, Brassolinae, Satyrinae, Morphinae. Of the socioeconomic and environmental Study it is observed, alone 12.9QO/o of the farmers is devoted to the livestock upbringing 1 vaccinate especially for the sector the Shainas and the Village Alfarillo, with a maximum of livestocks of 25 and a minimum of one. The residents are consciences ofthis problem and they manifest their limitations and the threat that it would be with the change of cultivations of coffee for grasses reducing the capacity of retention of the resource hydrological by m~s of the biological mattress. The cultivation of coffee is the biggest agricultura! work that you/they carry out and it is sold in its majority in the companies and middlemen of the city of ~oyobamba, the varieties of coffee that are cultivated are Caturra, Catimor that are cultivations in its 6 year-old recent great extension. One has the national variety that embraces the biggest extension in the area and they exist in you stain them observables in the area they have an antiquity from 15 to 20 years. The production on the average gives 17.56 qq/ha. in parchment. The months of crop they go in the low parts ofMarch to June and the high parts ofMay to September. The number average of sowed hectares of coffee for farrner this in 2.5 there are. Inside the plagues and illnesses of the cultivation of coffee the present affectation is 8.41 % for Arañero (Corticium kileroga), 10.03% Dril! (Hypothenemus hampei), 8.09% Eye of Chicken (Mycena citricolor), 1.94% Roya (Hernileia vastratix), 5.83% for Black Foot (Rossellinianm sp.), and 65. 70% of cultivations that are not relatively affected. The organizations that support and they manifested their commitment in forrning synergies for the rational use of the resources they are: Provincial municipality of Moyobamba, German Technical Cooperation (GTZ-PDRS), 1 Govem Regional of San Martin - 1 Project Special High May (PEAM), 1 Project Andean Basins, Ministry of Agriculture Handling ofNatural Resources ofthe Sierra South (MARENASS), National Institute of Natural Resources (INRENA), Entity Prestadora of Services of Reparation xviii \foyobamba EPS-M. SRLtda, Rural Beats, Committee of Administration of Areas of ~fonicipal Conservation, Units ofLocal Administration. The objective of the Plan Teacher is to be a document it guides, for the administration and administration of the Area of Conservation Municipal Almond, on tbe part of the Municipal Government of Moyobamba through the Management of ~iunicipal Services and environment, and the Entity Prestadora of Services of Reparation SRLtda, through the Prograrn of Preservation of the environrnent that is in mrrow coordination with the Units of Local Administration, the Rural Beats and Committees of Autofensa and Development. It will be an instrument of local administration, dynamics with a period of four year-old validity. The priorities identified in the process that you/they are the tree Almond (Pnmus amygdalus), the butterfly Maria Elena (Morpho menealus), the bird Huauto or mount turkey (Aburri aburria) and the Bromélida (Tillandsia mureana). By means of the process you Zonificacion and based on the Article 23º of the law of protected natural areas 26834. lt is contemplated the following areas: Area of Sttict Protection Strict 440.78 has, Area of Tourist and Recreational Use 83.26 has, Area ofspecial Use 23.14 has, Area ofRecovery 130.99 has. It was possible to identify me following programs: lt prograrns ofHandling ofNatural and Cultural Resources, it Programs of Use Public, it Programs from Support to the Administration, Prograrn of ~.lonitored and Evaluation. With an 1 mount for four years of 135 050.000 New Suns.